«On the Origin of Species»: Didactic transposition to the curriculum and Portuguese science textbooks (1859-1959) - Cavadas, Bento (2017)
This research aimed to contribute to the history of the teaching of Darwinism in the Portuguese curriculum from 1859 to 1959. To this end, it was analysed the didactic transposition of the book On the Origin of Species for standards and textbooks of Natural Sciences of secondary education. This study showed that some standards did not address Darwinism (Standards of 1856, 1872, 1880, 1886, 1926 and 1929), while others only prescribed the study of some subjects of Darwinism (Standards of 1889 and 1905). The standards of 1895 were the ones that addressed more Darwinists ideas in the 19th century. In the 20th century, the overall approach to Darwinism was related to the study of transformist ideas (Standards of 1919) or evolution (Standards of 1936 and 1954). However, even when the respective standards did not make that prescription, the major part of textbooks addressed the mechanisms of Darwinian evolution: adaptation, variability, growth correlations, heredity, natural selection, vital competition, geographic isolation and sexual selection.